'MobileMyArab Game' Berdasarkan Sukatan Pelajaran JAIS - Mohamed Masrop, Noor Azli; Sahrir, Muhammad Sabri; Zainuddin, Ghazali; Ramlan, Siti Rosilawati; Ishak, Siti Haffawati; Abdul Latif, Jahirah Juwairiyah (2019)
A poster presentation in INNOVATE@ILEC 2019 (International Language and Education Conference organised by Faculty of Major Language Studies, Universiti Sains Islam Malaysia (USIM) and Fakultas Pendidikan Bahasa, Universitas Muhammadiyyah Yogjayarta (UMY).